Simple Question Complicated Answer - 2

Geometry Level 5

A parabola lies completely in the first quadrant and is tangent to the line y = 3 x y = \sqrt{3} x at ( 3 , 3 3 ) (3, 3 \sqrt{3}) and to the x-axis at ( 4 , 0 ) (4, 0) . Find the distance between the vertex of the parabola and its focus (the focal distance).


The answer is 0.652.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

David Vreken
Jul 16, 2019

Label the three points A ( 0 , 0 ) A(0, 0) , B ( 3 , 3 3 ) B(3, 3\sqrt{3}) , and C ( 4 , 0 ) C(4, 0) , and draw B C BC . By the distance formula, the sides of A B C \triangle ABC are A C = 4 AC = 4 , A B = 6 AB = 6 , and B C = 2 7 BC = 2 \sqrt{7} . Now rotate and shift the diagram so that the parabola has a vertical axis and a vertex at ( 0 , 0 ) (0, 0) , for an equation of y = a x 2 y = ax^2 , while still preserving the focal distance and triangle lengths of A B C \triangle A'B'C' .

Let B B' be ( u , a u 2 ) (u, au^2) and C C' be ( v , a v 2 ) (v, av^2) . The slope at B B' is y = 2 a u y' = 2au so its tangent line is y = 2 a u x a u 2 y = 2aux - au^2 . Likewise, the tangent line at C C' is is y = 2 a v x a v 2 y = 2avx - av^2 . These tangent lines intersect at A ( 1 2 u + 1 2 v , a u v ) A'(\frac{1}{2}u + \frac{1}{2}v, auv) .

Using the distance formula for each side of A B C \triangle A'B'C' gives

B C 2 = ( u v ) 2 + ( a u 2 a v 2 ) 2 = 28 B'C'^2 = (u - v)^2 + (au^2 - av^2)^2 = 28

A C 2 = ( 1 2 u 1 2 v ) 2 + ( a u v a v 2 ) 2 = 16 A'C'^2 = (\frac{1}{2}u - \frac{1}{2}v)^2 + (auv - av^2)^2 = 16

A B 2 = ( 1 2 u 1 2 v ) 2 + ( a u v a u 2 ) 2 = 36 A'B'^2 = (\frac{1}{2}u - \frac{1}{2}v)^2 + (auv - au^2)^2 = 36

which for a > 0 a > 0 has a solution of a = 19 19 216 a = \frac{19\sqrt{19}}{216} .

Therefore, the focal distance is p = 1 4 19 19 216 = 54 19 361 0.652 p = \frac{1}{4 \cdot \frac{19\sqrt{19}}{216}} = \frac{54 \sqrt{19}}{361} \approx \boxed{0.652} .

Very Elegant. Just wondering, how did you solve the three equations in the three unknowns. Did you do it yourself, or did you use Wolframalpha.com or a similar package ?

Hosam Hajjir - 1 year, 11 months ago

Log in to reply

For this one I used wolframalpha.com, but for other problems I sometimes use the rref matrix function on a graphing calculator (if the equations are linear) and sometimes I just solve them myself.

David Vreken - 1 year, 11 months ago
Hosam Hajjir
Jul 16, 2019

This problem lends itself to the Bezier curve method, which states the the parametric equation of the given parabola is,

p ( t ) = p 0 ( 1 t ) 2 + 2 p 1 t ( 1 t ) + p 2 t 2 p(t) = p_0 (1 - t)^2 + 2 p_1 t (1 - t) + p_2 t^2

where p 0 p_0 and p 2 p_2 are the tangent points of the parabola and p 1 p_1 is the intersection point of the two tangent lines.

So we can take p 0 = ( 4 , 0 ) p_0 = (4, 0) , and p 2 = ( 3 , 3 3 ) p_2 = ( 3, 3 \sqrt{3} ) and p 1 = ( 0 , 0 ) p_1 = (0, 0) . Substituting this,

p ( t ) = ( 4 ( 1 t ) 2 + 3 t 2 , 3 3 t 2 ) p(t) = ( 4 (1 - t)^2 + 3 t^2 , 3 \sqrt{3} t^2 )

= ( 4 8 t + 7 t 2 , 3 3 t 2 ) = ( 4 - 8 t + 7 t^2 , 3 \sqrt{3} t^2 )

= q 0 + q 1 t + q 2 t 2 = q_0 + q_1 t + q_2 t^2

where q 0 = ( 4 , 0 ) , q 1 = ( 8 , 0 ) , q 2 = ( 7 , 3 3 ) q_0 = (4, 0) , q_1 = (-8, 0 ), q_2 = (7, 3 \sqrt{3} )

Now we'll apply a small trick to orthogonalize the two axes spanning p ( t ) p(t) . Since the parameter t t can be any real number, we can, just as well, use ( t t 0 ) (t - t_0) instead of t t , where t 0 t_0 is some fixed real number. Thus

p ( t ) = q 0 + q 1 ( t t 0 ) + q 2 ( t t 0 ) 2 p(t) = q_0 + q_1 (t - t_0) + q_2 (t - t_0)^2

= ( q 0 q 1 t 0 + q 2 t 0 2 ) + ( q 1 2 q 2 t 0 ) t + q 2 t 2 = (q_0 - q_1 t_0 + q_2 t_0^2 ) + ( q_1 - 2 q_2 t_0 ) t + q_2 t^2

Now, we'll select t 0 t_0 such that,

( q 1 2 q 2 t 0 ) q 2 = 0 (q_1 - 2 q_2 t_0) \cdot q_2 = 0

which is always possible by choosing t 0 = 1 2 ( q 1 . q 2 ) ( q 2 . q 2 ) t_0 = \dfrac{1}{2} \dfrac{ (q_1 . q_2) }{ (q_2 . q_2) } , then

p ( t ) = w 0 + w 1 t + w 2 t 2 p(t) = w_0 + w_1 t + w_2 t^2

where,

w 0 = q 0 q 1 t 0 + q 2 t 0 2 w_0 = q_0 - q_1 t_0 + q_2 t_0^2

w 1 = q 1 2 q 2 t 0 w_1 = q_1 - 2 q_2 t_0

w 2 = q 2 w_2 = q_2

and with the above value of t 0 t_0 , we have w 1 w_1 orthogonal to w 2 w_2 . If we now define unit vectors along w 1 w_1 and w 2 w_2 as follows

u 1 = w 1 / w 1 u_1 = w_1 / | w_1 | and u 2 = w 2 / w 2 u_2 = w_2 / | w_2 | , then

p ( t ) = w 0 + w 1 u 1 t + w 2 u 2 t 2 p(t) = w_0 + | w_1 | u_1 t + | w_2 | u_2 t^2

since u 1 u_1 and u 2 u_2 are unit vectors and are orthogonal, they specify a reference frame, hence

p ( t ) w 0 = [ u 1 , u 2 ] ( x , y ) p(t) - w_0 = [u_1 , u_2 ](x, y)

with x = w 1 t x = | w_1 | t , and y = w 2 t 2 y = | w_2 | t^2

thus ( x w 1 ) 2 = y w 2 (\dfrac{x}{ | w_1 |} )^2 = \dfrac{y}{ | w_2 | }

is our equation of the parabola; it follows that y ( w 1 2 w 2 ) = x 2 y ( \dfrac{| w_1 |^2 }{ | w_2 | } ) = x^2

Comparing this with the standard equation of a parabola, which is 4 p y = x 2 4 p y = x^2 , it follows that,

4 p = w 1 2 w 2 4 p = \dfrac{ | w_1 |^2 }{ | w_2 | }

which imples that p = 1 4 w 1 2 w 2 p = \dfrac{1}{4} \dfrac{ | w_1 |^2 }{ | w_2 | }

The rest is straight forward computations.

Iliya Hristov
Mar 22, 2020

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...